The preparations of fluorographene nanosheets and research in tribological properties in high vacuum - Lili Zhang; Zhengrui Zhang; Xi’an Gao; Siti Jahara Matlan; Nazaruddin Abd Taha (MDPI, 2023)
In this study, fluorographene nanosheets (FG nanosheets) were prepared via the solventultrasonic exfoliation method. The fluorographene sheets were observed using field-emission scanning electron microscopy (FE-SEM). The microstructure of the as-prepared FG nanosheets was characterized by X-ray diffraction (XRD) and a thermal analyzer (TG). The tribological properties of FG nanosheets as an additive in ionic liquids in high vacuum were compared to that of ionic liquid (IL) with graphene (IL-G). The wear surfaces and transfer films were analyzed via an optical microscope, Raman spectroscopy, scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS). The results show that FG nanosheets can be obtained from the simple solventultrasonic exfoliation method. The prepared G nanosheets are a sheet, and the longer the ultrasonic time is, the thinner the sheet is. Ionic liquids with FG nanosheets had low friction and a low wear rate under high vacuum conditions. The improved frictional properties were attributed to the transfer film of FG nanosheets and more formation film of Fe-F.